America at a crossroads. Struggle for the soul of Islam : inside Indonesia [videorecording (DVD)]. - MacNeil, Robert, 1931- (PBS Home Video, 2007)
An inside look at how a fledgling democracy is struggling to control the rise of religious extremism.